Colon specific drug delivery of tramadol HCl for chronotherapeutics of arthritis - Kadiyam, Rajyalakshmi; Muzib, Y. Indira (International Journal of Pharmaceutical Investigation)
Objective: The objective of present work is to develop and evaluate a matrix system for Chronotherapeutic delivery of centrally acting of opioid analgesic (tramadol HCl) to treat nocturnal symptoms of arthritis using almond gum as carrier. Materials and Methods: Matrix tablets of tramadol HCl were prepared by using 30, 40, 50, 60 and 70% w/w of tablet of gum badam as carrier by wet granulation technique. These tablets were compression coated with eudragit S100 to prevent drug release in stomach. All formulations were evaluated for hardness, friability, weight variation, drug content, in vitro and in vivo studies. The almond gum was characterized by viscosity measurements and Fourier transform infrared analysis. The coated (FC1 to FC5) and uncoated tablets (F1 to F5) were evaluated for in vitro release of tramadol HCl after sequential exposure to pH 1.2, pH 7.4 and pH 6.8 respectively for 2 h, 3 h and 19 h in the absence as well as presence of rat caecal content and the corresponding data was fitted to popular release kinetic equations in order to evaluate the release mechanisms-kinetics. The selected formulation was subjected to in vivo targeting efficacy studies by roentgenography technique. Results and Discussion: In vitro release studies indicated that the matrix tablets (F1 to F5) failed to control the drug release in the physiological environment of stomach and small intestine. On the other hand, compression coated formulations were able to protect the tablet cores from premature drug release. Presence of rat caecal content enhances the drug release from the tablets as the concentration of polymer increased, drug release was found to be retarded. The release of tramadol from all the formulation followed zero order with non fickian diffusion. X-ray studies confirmed that the tablet successfully reached colon without getting disintegrated in upper gastrointestinal tract. Conclusion: Based on the results, selective delivery of tramadol HCl to the colon could be achieved using 60% w/w (FC4) of almond gum matrix tablets compression coated with eudragit S100.
Keywords: Eudragit S100; gum almond; rat caecal content; roentgenography; tramadol HCl